Quality management: where is the evidence?: Developing an indicator-based approach in Kenya - Prytherch, Helen; Marx, Irmgard; Szecsenyi, Joachim; Marx, Michael (International journal for quality in health care, 2017)
AbstractIntroduction. The 2030 Sustainable Development Agenda emphasizes the importance of quality of care in the drive to achieve universal health coverage.